Subjectivity as a challenge to adulthood - Krystyna Najder-Stefaniak (Studia z Teorii Wychowania)
The author draws attention to the specificity of subjectivity and its importance for human security. It shows that we have an influence on the scope and quality of subjectivity.The concept of a relatively isolated system helps to understand the subject. They were introduced by Roman Ingarden looking for ontical grounds of responsibility. According to Ingarden, the responsible person contacts the environment, but the source of the activity is within him. This means that we are not doomed to react, that we can act. We have an impact on the quality of the entity and, consequently, the scope and quality of subjectivity.